1988
DOI: 10.1021/je00052a019
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-liquid equilibria of nitrogen-hydrocarbon systems at elevated pressures

Abstract: The phase equilibria behavior of nitrogen + hydrocarbon binary, ternary, and quaternary systems was studied. Measurements were made over the temperature range from 305.4 K (90 °F) to 373.2 K (212 °F) at pressures up to 35.85 MPa (5200 psia). The binary systems studied Included nitrogen + n -heptane, nitrogen + n -octane, nitrogen + n -nonane, nitrogen + n -decane, nitrogen + n-dodecane, nitrogen + benzene, and nitrogen + toluene. The methane + n -butane + n -decane, nitrogen + n -butane + n-decane, and nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 6 publications
4
30
0
Order By: Relevance
“…Even though all k ij values predict the trends quite well, it is observed that both temperature dependent and average k ij values (Gao, Robinson Jr., & Gasem, 1999) predict the liquid-phase nitrogen mole fraction more accurately against the experimental data (Gao, Robinson Jr., & Gasem, 1999), when compared to that predicted using the k ij value reported in Curtis & Farrell (1992). A comparison between theoretical model predictions of the mole fraction of ndodecane in the liquid-phase against the experimental data of Llave & Chung (1988) is shown in Figure 2. As the ambient pressure increases, the liquid-phase mole fraction of n-dodecane decreases due to additional quantities of dissolved ambient gas in the liquid-phase.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Even though all k ij values predict the trends quite well, it is observed that both temperature dependent and average k ij values (Gao, Robinson Jr., & Gasem, 1999) predict the liquid-phase nitrogen mole fraction more accurately against the experimental data (Gao, Robinson Jr., & Gasem, 1999), when compared to that predicted using the k ij value reported in Curtis & Farrell (1992). A comparison between theoretical model predictions of the mole fraction of ndodecane in the liquid-phase against the experimental data of Llave & Chung (1988) is shown in Figure 2. As the ambient pressure increases, the liquid-phase mole fraction of n-dodecane decreases due to additional quantities of dissolved ambient gas in the liquid-phase.…”
Section: Resultsmentioning
confidence: 92%
“…The percentage deviations between the experimental data and the theoretical predictions using different k ij values are shown in Table 2, which consolidates all the above results. The predictions using different EOS such as RK-EOS, SRK-EOS and PR-EOS are compared with the experimental data reported in Gao, Robinson Jr., & Gasem (1999) and Llave & Chung (1988) Gao et al (1999) for a nitrogen-n-dodecane binary system in thermodynamic equilibrium at different temperatures (a) 327.6 K (b) 344.3 K and (c) 366.5 K.…”
Section: For a Nitrogen-n-dodecane Binary System In Thermodynamic Equmentioning
confidence: 99%
See 3 more Smart Citations